The essence of pedagogical psychology of the concept of research activity in the project training of educators - Мамытбаева, Жанат; Төлешова, Улмекен; Боранбаева, Ақтолқын (Pedagogy and Psychology, 2022)
To consider the issue of the formation of research activities in the training of future teachers in preschool educational institutions with the disclosure of the essence of project-based learning. In the field of pedagogical education, research activity is of priority importance in achieving results. Activity is the philosophy and methodology of research, most often used in research in the social sciences, psychology and pedagogy. Future teachers should be able to solve complex problems in research activities based on project-based learning. The cognitive, social activity of university students is strengthened, the interest in learning increases, in the process of project training of future teachers-educators based on project activities, the project method, Design, design technology, conceptual foundations of the project method, the basic requirements for the use of the project method, types of project, the didactic value of the project in design methods. When studying activities in processes related to the process of interactive research in solving problems as a result of analysis or data to understand the main reasons for predicting personal and organizational changes in the future. The process of developing new scientific knowledge in scientific research, a type of cognitive activity. In the study of activity, practitioners considered one of the types of problem research as an empirical process with their experience. Purposefulness creation and exchange of knowledge in the field of social sciences.The study is characterized by objectivity, reproducibility, evidence, accuracy. It has two interrelated levels: empirical and theoretical.